Effect of acotiamide on gastric emptying in healthy adult humans. (December 2014) - Zai, Hiroaki; Matsueda, Kei; Kusano, Motoyasu; Urita, Yoshihisa; Saito, Youichi; Kato, Hiroki
Abstract Background Acotiamide is a first‐in‐class drug that is used to treat functional dyspepsia (FD). It is considered that acotiamide acts as an antagonist on muscarinic autoreceptors in the enteric nervous system and inhibits acetylcholinesterase activity. We examined the effect of acotiamide on gastric emptying in healthy adult humans. Materials and methods Twelve healthy adult males were enrolled in this double‐blind crossover study. Acotiamide or placebo was administered orally in the 12 subjects 30 min before ingestion of a nutritional liquid meal (400 Kcal/400 mL). Six of the 12 participants took 100 mg of acotiamide or placebo, and six of the 12 participants took 300 mg of acotiamide or placebo in a double‐blind crossover fashion. All subjects underwent measurement of gastric emptying by the 13C breath test. Results After the meal with placebo was ingested, the %dose/h curve ascended. The %dose/h curve after a meal with 100 or 300 mg of acotiamide ascended in an identical manner compared with the results with placebo. No significant differences were observed at any studied time point, and there were no significant changes in gastric emptying parameters (gastric emptying coefficient, t‐1/2ex and t‐lag ex). Conclusions A single administration of 100 or 300 mg of acotiamide did not affect gastric emptying after a liquid meal in healthy adult humans. Acotiamide has profound effects on restoring delayed gastric emptying and impaired accommodation in patients with FD but may have no effect on gastric emptying in healthy subjects. Such pharmacological actions have not been observed in previous gastroprokinetic studies.